Agenesis of premolar associated with submerged primary molar and a supernumerary premolar: An unusual case report - S. V. S. G. Nirmala; C Sandeep; N Sivakumar; M S Babu; V Lalitha (Wolters Kluwer Medknow Publications, 2012)
The combination of submerged primary molar, agenesis of permanent successor with a supernumerary in the same place is very rare. The purpose of this article is to report a case of submerged mandibular left second primary molar with supernumerary tooth in the same region along with agenesis of second premolar in an 11-year-old girl, its possible etiological factors, and a brief discussion on treatment options.